2006
DOI: 10.1109/led.2006.870242
|View full text |Cite
|
Sign up to set email alerts
|

Ge n-MOSFETs on lightly doped substrates with high-/spl kappa/ dielectric and TaN gate

Abstract: In this letter, we report successful fabrication of Germanium n-MOSFETs on lightly doped Ge substrates with a thin HfO 2 dielectric (equivalent oxide thickness 10 8 A) andTaN gate electrode. The highest peak mobility (330 cm 2 /V s) and saturated drive current (130 A/sq at -= 1 5 V) have been demonstrated for n-channel bulk Ge MOSFETs with an ultrathin dielectric. As compared to Si control devices, 2.5 enhancement of peak mobility has been achieved. The poor performance of Ge n-MOSFET devices reported recently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 14 publications
0
29
0
Order By: Relevance
“…[4][5][6] The poor device performance is likely caused by the presence of defects near the semiconductor/dielectric interface, such as germanium dangling bonds (DBs) or vacancies, making the study and characterization of these defects a much needed and timely task.…”
Section: 3mentioning
confidence: 99%
“…[4][5][6] The poor device performance is likely caused by the presence of defects near the semiconductor/dielectric interface, such as germanium dangling bonds (DBs) or vacancies, making the study and characterization of these defects a much needed and timely task.…”
Section: 3mentioning
confidence: 99%
“…Feverish research efforts were carried out to identify dielectrics suitable for Ge passivation, since native oxide of Ge (GeO x ) results in poor electrical properties. Previous intense research work on Ge MOS devices has concluded that interfacial layers such as GeO x N y [1,2] or epi-Si/SiO 2 [3,4] are required for effective passivation of Ge and for preventing inter-diffusion between Ge and the subsequent deposited high-k dielectrics.…”
Section: Introductionmentioning
confidence: 99%
“…So far, the mobility in fabricated Ge MOSFETs has been disappointing [10,11], possibly due to processing issues. Hence our results set an upper limit on the mobility and comparison to fabricated Ge devices is not yet meaningful.…”
Section: Resultsmentioning
confidence: 99%